EN-33: preliminary study of electrodialysis for enrichment of ammonium from wastewater - Choo, Bryan Yee Chian (Nanyang Technological University, 2022)
The electrodialysis (ED) process is a process that utilises IEMs (ion-exchange membranes) for resource recovery and a means of obtaining clean water. This project was created to investigate the effect of change in total effective area of IEMs in the ED process on the recovery efficiency and nutrient recovery process, as well as investigate the impact of leakages of ions in the electrode chambers on the overall recovery efficiency. A synthetic amalgamation of key components NH4Cl, KH2PO4, NaHCO3, MgCl2. 6H2O, CaCl2. 2H2O, was used as domestic wastewater (DW) for the purposes of this project. An ED stack was setup, and results from the ED process were analysed. It is found that by increasing the number of cell pairs, rate of reaction as well as concentration of ammonium ions in the concentrate chamber increases, while leakage into the electrode chamber is reduced, directly translating to a more efficient ammonium collection in the concentrate chamber.